VARIETY OF ENGLISH LEARNING MEDIA TECHNOLOGY: VOICES FROM NOVICE LEARNERS - Dadang Solihat; Fahrus Zaman Fadhly; Marwito Wihadi (English Review: Journal of English Education, 2023)
The existence of technological media in the learning process has its own roles and challenges in this era of disruption. The purpose of this study is the extent to which the use of technological media supports learning English in junior high schools and the equivalent. The research method used is the survey method. The research was conducted in 36 public and private junior high schools and Madrasah Tsanawiah in Kuningan Regency by collecting data through a Google form questionnaire. The results obtained turned out that of the 59 teachers who filled out the Google form, as many as 86.4% of English teachers used laptops, handphones with infocus, frequently used applications, Whatsapp 28.8%, Power Point 22%, Youtube 32.2%, and E-learning 16.9%. However, 88.1% stated that teachers had not maximized the use of technological media in learning English. On the other hand, from 200 students grade seven (19%), grade eight (40%) and grade nine (41%), there are 54.5% did not use technology media, 37% used laptop, infocus, and Handphone, and 8.5% used laboratorium.